Difference between revisions of "008A Sample Final A, Question 12"

From Math Wiki
Jump to navigation Jump to search
 
Line 2: Line 2:
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
!Foundations
+
!Foundations:  
 
|-
 
|-
 
|1) f(x + h) = ?
 
|1) f(x + h) = ?
Line 18: Line 18:
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
! Step 1:
+
!Step 1:  
 
|-
 
|-
 
|The difference quotient that we want to simplify is <math>\frac{f(x + h) - f(x)}{h} = \left(\frac{2}{3(x + h) + 1} - \frac{2}{3x + 1}\right) \div h</math>
 
|The difference quotient that we want to simplify is <math>\frac{f(x + h) - f(x)}{h} = \left(\frac{2}{3(x + h) + 1} - \frac{2}{3x + 1}\right) \div h</math>
Line 24: Line 24:
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
! Step 2:
+
!Step 2: &nbsp;
 
|-
 
|-
 
|Now we simplify the numerator:  
 
|Now we simplify the numerator:  
Line 37: Line 37:
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
! Arithmetic:
+
!Step 3: &nbsp;
 
|-
 
|-
 
|Now we simplify the numerator:  
 
|Now we simplify the numerator:  
Line 50: Line 50:
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
! Final Answer:
+
!Final Answer: &nbsp;
 
|-
 
|-
 
|<math>\frac{-6}{(3(x + h) + 1)(3x + 1))}</math>
 
|<math>\frac{-6}{(3(x + h) + 1)(3x + 1))}</math>
 
|}
 
|}
 
[[008A Sample Final A|<u>'''Return to Sample Exam</u>''']]
 
[[008A Sample Final A|<u>'''Return to Sample Exam</u>''']]

Latest revision as of 22:59, 25 May 2015

Question: Find and simplify the difference quotient for f(x) =

Foundations:  
1) f(x + h) = ?
2) How do you eliminate the 'h' in the denominator?
Answer:
1).
2) The numerator of the difference quotient is   so the first step is to simplify this expression. This then allows us to eliminate the 'h' in the denominator.

Solution:

Step 1:  
The difference quotient that we want to simplify is
Step 2:  
Now we simplify the numerator:
Step 3:  
Now we simplify the numerator:
Final Answer:  

Return to Sample Exam